2021
DOI: 10.1093/nsr/nwab124
|View full text |Cite
|
Sign up to set email alerts
|

Genomic diversity and post-admixture adaptation in the Uyghurs

Abstract: Population admixture results in genome-wide combinations of genetic variants derived from different ancestral populations of distinct ancestry, thus providing a unique opportunity for understanding the genetic determinants of phenotypic variation in humans. Here, we used whole-genome sequencing of 92 individuals with high coverage (30–60×) to systematically investigate genomic diversity in the Uyghurs living in Xinjiang, China (XJU), an admixed population of both European-like and East-Asian-like ancestry. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 73 publications
1
36
0
Order By: Relevance
“…Chromosome-wide genetic diversity was estimated within sliding windows of 10 kb in length, advanced by 5 kb by estimators of nucleotide diversity ( θ π ) and numbers of segregating sites ( θ K ) using publicly available software [ 60 ]. Tajima's D statistics [ 27 ], Fay and Wu's H statistics [ 37 , 38 ], H12 statistics [ 39 , 61 , 62 ], Fu and Li's D statistics [ 43 ], and Fu and Li's F statistics [ 43 ] were calculated in the same way.…”
Section: Methodsmentioning
confidence: 99%
“…Chromosome-wide genetic diversity was estimated within sliding windows of 10 kb in length, advanced by 5 kb by estimators of nucleotide diversity ( θ π ) and numbers of segregating sites ( θ K ) using publicly available software [ 60 ]. Tajima's D statistics [ 27 ], Fay and Wu's H statistics [ 37 , 38 ], H12 statistics [ 39 , 61 , 62 ], Fu and Li's D statistics [ 43 ], and Fu and Li's F statistics [ 43 ] were calculated in the same way.…”
Section: Methodsmentioning
confidence: 99%
“…They followingly migrated out of Africa around 50 thousand years ago and evolved in concert with the complicated interplay of gene flow and adaptive selection during the peopling of Eurasia, Oceania, and America ( Bergstrom, et al, 2020 ; Wang et al, 2021a ). Genomic studies have demonstrated the pervasiveness of population differentiation and genetic admixture between long-isolated ethnic groups ( Bergstrom et al, 2020 ; Pan et al, 2022 ). Extensive population bottleneck, adaptive evolution in changing environments, and introgression from archaic hominins further shaped the complicated patterns of human genetic heritage.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence to suggest that the differences in the susceptibility of many common and rare diseases are primarily attributed to human populations’ diverse cultural, environmental, demographic, and genetic histories. The comprehensive understanding of fine-scale population evolutionary history will gradually change our understanding of the genetic architecture of diseases ( Timpson et al, 2018 ; Benton et al, 2021 ; Pan et al, 2022 ). Thus, there is an urgent need to expand genetic research to populations with different ancestries.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to large-scale clinical genomic cohorts that have advanced the understanding of genetic determinants of disease susceptibility and genetic background of Han Chinese populations, many molecular anthropological and evolutionary genetic studies started to focus on the genetic diversity of ethnolinguistically diverse populations in China, such as the characterization of population history and biological adaptation of Tibetan [11][12][13][14][15] and Sherpa [16] from the Tibetan Plateau and the dissection of Eurasian admixture signature in Uyghur [17] and Hui [18]. However, we should note that most previous genetic studies were conducted based on forensic-related genetic markers [Short Tandem Repeats (STRs), Insertion/Deletions (InDels), Micro-Haplotypes, ancestry-informative SNPs (AISNPs), and other Xor Y-linked markers] or lower-density SNPs (50K ~ 100K) in the merged dataset [19][20][21].…”
Section: Introductionmentioning
confidence: 99%